A CLINICAL STUDY ON EVALUATION OF POST CESARIAN BREAST MILK SECRETION WITH SHATAVARIKALPA: AYURVEDIC FORMULATIONS - Surendra Mohite, *Swati; Anil Singh, Anamita (International Journal of Ayurveda and Pharma Research, 2018)
Sutika is the stage as placenta out from the womb for 1st to 6th weeks. Sutika is the condition in which she had feeling of mother and due to this Prakrut vata helps to initiation of Breast milk secretion, for all this there is changes takes place in hormone, this all done by Prakrut vata dosha and balance of Kapha doshas. Shushrut mentioned Mudhagarbha in which Vipatan (incision) done by Vaidyas into uterus to take out baby from womb, after expulsion of placenta the lady is called Sutika (puerperial stage). Breast secretion were observed in post caesarian patient after 3-4 days, as baby not delivered by Prakrut prasava. The Ayurvedic formulation having property to provide stability to the mother in Sutika awstha, digestive Rasa dhatu and provide proper digestive milk nutrients to the baby for their proper growth and development. Galactogogues are substances used to induce, maintain, and increase milk production, both in humanclinical condition(like noninfectious agalactias and hypogalactias). Shatavari is a good herbal galactogogues which increase milk production after post caesarian section. Aim: To study the evaluation of Breast milk secretion with Ayurvedic formulations and to avoid modern medicines in post cesarian section cases side effects on breast secretion and use of antacid property of Shatvari kalpa. Methodology: Oral medication Shatavarikalpa were administered to the patient of post cesarian, after two days when shifted to oral diet for 1 month. Result: A total no. of 100 patients were included in this study out of which 50 patients were treated with Ayurvedic formulation and 50 were treated with modern analgesics with antibiotics. In trial group on day 7th 41(82%) patients having good secretion and on day 15th 44 (88%) patients good secretion were observed. In control group on day 7th 31 (62%) patients having good secretion and on day 15th 35 (70%) patients were observed. Average duration of stay at the IPD was 7 days and follow upon 15th day. Conclusion: The administration of Shatavarikalpa helps in adequate milk secretion for neonate growth. This combination maybe an effective alternative for act as an antacid treatment administered to patients undergoing post caesarian section cases.